Impact of swallowing function and nutritional status on quality of life among nasopharyngeal carcinoma patients in Malaysia - Ali, Hatikah (2019)
Nasopharyngeal carcinoma (NPC) patients might experience poor quality of life (QOL) as the location of the tumour severely affects their eating, swallowing, and breathing functions. Moreover, the treatment of radiation and/ or surgical therapy for NPC patients affects one or more phases in swallowing which might eventually lower their QOL. In Malaysia, NPC is the fourth (5.2%) most common cancer among Malaysians and the third (8.4%) most common cancer among males. This study aimed to assess the relationship of swallowing function and nutritional status with QOL among NPC patients as measured by three standard tools, the University of Washington Quality-of- Life Questionnaire (UW-QOL) with 12 different domains, the Swallow Qualityof- Life Questionnaire (SWAL-QOL) with 11 different domains and Subjective Global Assessment (SQA). This is a cross-sectional study design and data collection was conducted in the period of six months from June 2018 to December 2018. This study employed a convenience sampling method for the selection of respondents. A total of 90 NPC patients (of age 18 years and above) who have visited the Otorhinolaryngology Clinic at Hospital Tuanku Ja’afar Seremban, Malaysia were selected. Data were analyses using the IBM SPSS (version 21) and involved descriptive and bivariate statistical test analysis. An independent t-test, and multiple linear regression were conducted to measure the relationship and factors that affect the QOL of NPC patients. A statistically significant was considered if p<0.05. It was observed that the dysphagia discreetly affects the patients' quality of life in relation to swallowing function with a total mean score of 63.97 ±SD 8.58. The fatigue domain of SWAL-QOL recorded the lowest mean score, followed by food selection domain of SWAL-QOL. In this present study, the data collection showed that swallowing problems affect the QOL of NPC patient negatively (p<.001). It was observed that the QOL score of well-nourished patients was significantly higher than the QOL score of mildly or moderately malnourished patients (p < .001). This finding of the study indicates that swallowing function have effect on nutritional status among NPC patients. As a recommendation, healthcare practitioners, such as nurses and dietitians, can conduct proper education or counseling on dysphagia and nutritional intake for NPC patients to attain a better health-related quality of life.